Endoscopic Supernumerary Canine Tooth Extraction in an Adult Presented with Acute Nasal Blockage : A Case Report - Mohd Salehuddin, Nur Syazwani; Ramli, Ramiza Ramza; Aziz, Azliana (International Journal of Human and Health Sciences (IJHHS), 2019)
Intranasal ectopic tooth, which can be derived from either supernumerary, deciduous or permanent tooth, is generally a rare event. Their existence can cause a wide array of complication such as epistaxis, nasal blockage, nasal pain, rhinosinusitis, septal deviation, septal abscess as well as oronasal fistula. We highlight a case of a canine supernumerary tooth that erupted at floor of nasal cavity, causing an acute unilateral nasal blockage, and managed successfully with an endoscopic nasal tooth extraction. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 235-237